MODEL PENGAMBANGAN RPP DAN SILABUS DENGAN MODEL INSIDE OUTSIDE CIRCLE (IOC) DALAM MENINGKATAN HASIL BELAJAR SISWA KELAS VIII SMP AL-FURQON TEBUIRENG JOMBANG - Khoirur Roziqin, Muhamad; Chafizh Nahdliyul Ibad, M. (ILJ: Islamic Learning Journal, 2023)
Learning Implementation Design and syllabus as a set of plans and arrangements regarding curriculum development, are basically one of the prerequisites in determining learning objectives and outcomes. Apart from learning tools, another thing that can improve student learning outcomes is the selection of the right learning model used by the teacher. The Inside Outside Circle (IOC) learning model is a learning model that stimulates active learning so as to improve student learning outcomes. The purpose of this study was to determine the use of lesson plans based on the Inside Outside Circle (IOC) learning model in Class VIII Language at Al Furqan Middle School and student learning outcomes using the Inside Outside Circle (IOC) learning model in Class VIII Language at Al Furqan Middle School. This study uses a research and development (R&D) approach. The results of this study were obtained in the form of validation results of the implementation of learning designs from 2 experts showing an average result of 3.84. Meanwhile, the results of the syllabus validation show the results of 3.37. Both of these results indicate that the learning device is feasible to use without revision. Student responses to Inside Outside Circle (IOC) learning showed very good results of 61%. In student learning outcomes, the average posttest score is greater than the pretest score so that the average student learning outcomes taught by the Inside Outside Circle (IOC) learning model produce better scores